2016
DOI: 10.1088/0957-0233/27/12/125202
|View full text |Cite
|
Sign up to set email alerts
|

Aerial wetting contact angle measurement using confocal microscopy

Abstract: A method is presented in which the wetting contact angle of a sessile drop is acquired aerially using confocal techniques to measure the radius and the height of a droplet deposited on a planar surface. The repeatability of this method is typically less than 0.25°, and often less than 0.1°, for droplet diameters less than 1 mm. To evaluate accuracy of this method, an instrument uncertainty budget is developed, which predicts a combined uncertainty of 0.91° for a 1 mm diameter water droplet with a contact angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The contact angle θ between the particles and the hydrophobic glass slides was measured using a scanning confocal microscope (Zeiss, Axio Observer 510 MP, objective lens MAG x63k Plan-Apochromat, 1.4 aperture), following a method described elsewhere . The measurements were made at approximately 40% RH.…”
Section: Methodsmentioning
confidence: 99%
“…The contact angle θ between the particles and the hydrophobic glass slides was measured using a scanning confocal microscope (Zeiss, Axio Observer 510 MP, objective lens MAG x63k Plan-Apochromat, 1.4 aperture), following a method described elsewhere . The measurements were made at approximately 40% RH.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported the use of laser scanning confocal microscopy (LSCM) technique to evaluate the wetting properties . Chesna et al exploited the confocal microscopy to determine the radius and height of small droplets (<1 mm), based on which the CA is computed using a spherical approximation of the droplet shape θ =cos11hdrd…”
Section: Definition Of Surface Wettability: Beyond General Classifica...mentioning
confidence: 99%
“…Based on previous measurements, the reactive uptake coefficient of O 3 on oleic acid, squalene, triolein, and canola oil is approximately 8.0 × 10 –4 , 4.0 × 10 –4 , 1.5 × 10 –5 , and 5 × 10 –4 , respectively (see Table S2). ,,,,, ,, Most previous studies have also reported the uptake coefficients of O 3 on unsaturated lipids to be independent of RH. ,,, Based on eq and the approximate reactive uptake coefficients mentioned above, the fraction of oleic acid, squalene, triolein, and canola oil reacted by the time the new phase was first observed was approximately 2–44% at low RH (Table ). At medium RH conditions, the fraction of unsaturated lipids reacted when the new phase was first observed was comparable to that at low RH conditions, except for squalene.…”
Section: Discussionmentioning
confidence: 99%